Developmental counseling and therapy - Ivey, Allen E.; Iver, Mary Bradford; Oldershaw, Bruce; Microtraining Associates (North Amherst, Mass. : Microtraining Associates [Distributor])
Developmental concepts are basic to all counseling and therapy. This program provides highly specific techniques which have been used with a variety of clients ranging from typical child and adolescent issues through problems of adult development including psychiatric in-patient settings
Disc 1. Introduction ; Overview-vignettes ; Assessing ; Positive asset search ; Assessing cognitive development ; Questions ; Comments -- Disc 2. Shomari-questions with elementary child ; Confrontation and confrontation impact scale ; Lifespan development ; Assessment and treatment planning ; Multicultural development ; Commentary on PTSD ; Integration of DCT
Title from title screen
Host: Allen Ivey
Keywords: Developmental therapy; Counseling -- Methods; Human development; Psychotherapy -- methods